TAFSIR AL-QUR’AN DAN KRITIK SOSIAL: Syu’bah Asa dalam Dinamika Tafsir al-Qur’an di Indonesia - Gusmian, Islah (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Institut Agama Islam Negeri (IAIN) Purwokerto, 2016)
This focus writing in this paper is contribution of Syu’bah Asa in the practice of Quranic tafseer in Indonesia via hisbook of Dalam Cahaya Al Qur’an. There three things studies in this article. First , themes has been discussed address to dialectical messages of God and reality of social politic. Second, communication strategy in writing this topic . Third, some driving forces. In this article, author will use discourse analysis Theo Van Leewen who concentrate in the process of Exclusion and inclusion of discourse subject. From th result of analysis, syu’abah strongly makes dialectical between text and social politic reality when interpretation written. He also did some critics of reality social politic, mentioned the subject , and case context openly. Paradigmatically, Syu’bah contributed an unique tradition in the dynamic of writing interpretation (tafseer) in Indonesia where interpretation as space for making social political critics.